Looking for reliable answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Get immediate answers to your questions from a wide network of experienced professionals on our Q&A platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
Answer:
x = -2
y = 10
Step-by-step explanation:
(0.3 + 0.7) x + (0.4 - 0.8) y = 0.8 - 6.8
x - 0.4 y = -6 → x = 0.4 y - 6
0.3 ( 0.4 y - 6) + 0.4 y = 0.8 → 0.12y +0.4y - 1.8 = 0.8
→ 0.52 y = 2.6 → y = 2.6/0.52 = 10
x - 0.4(10) = -6 → x = -2
Step-by-step explanation:
0.3x + 0.4y = 0.8 /×2
0.7x - 0.8y = -6.8
1. 0.6x + 0.8y = 1.6
2. 0.7x - 0.8y = -6.8
1+2 : 1.3x + 0y = -5.2
1.3x = -5.2
x = -5.2÷1.3
x = -4
x -> 1 : 0.6 × -4 + 0.8y = 1.6
-2.4 + 0.8y = 1.6
0.8y = 4
y = 4÷0.8
y = 5
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.